6) It has one solution 7) infinite solution
Step-by-step explanation:
3/4 (x-1) - 1/2 = 2(1-3x)
By expanding:
![\begin{gathered} \frac{3x\text{ -3}}{4}-\text{ }(1)/(2)=\text{ 2 - 6x} \\ \frac{3x\text{ -3 -2}}{4}=\text{ 2-6x cross multiply} \\ 3x\text{ -5 = 4(2-6x)} \\ 3x\text{ -5 = 8 -24x} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iigbkl3m7yrj4q5y93jcnn6wq80os9uh3a.png)
By collecting like terms:
![\begin{gathered} 3x\text{ + 24x = 8+ 5} \\ 27x\text{ = 13} \\ x\text{ = }(13)/(27) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5zr6rw4f6o32cv0702sr7y1slb0j9l2ysa.png)
To determine what category it belongs, we need to understand our variable (x) is equal to a value (13/27). When this happens, we say it has one solution.
7) 2x + 4 = x + x + 3+1
2x + 4 = 2x +4
2x-2x = 4-4
0 = 0
When we have the right side of the equation equal to the left side, then it has infinite number of solution.